Analysis of Student Worksheet Needs in Green Chemistry Based Physics Chemistry Practicum - Herliani, Firmalia; Sanjaya; Hadeli M; Rahmat Zikri; Fricila Sasqia; Irma Amelia; Chindy E Putri; Nabila Z Hanani; Fatma Aningsih (Orbital: Jurnal Pendidikan Kimia, 2025)
Sustainability issues in chemistry laboratories are increasingly important to address, particularly because practicum activities often generate hazardous waste that can negatively affect both health and the environment. One approach that can be applied in chemistry education to reduce such risks is the implementation of green chemistry principles. In this context, the availability of learning materials that align with environmentally friendly practices is essential, including Student Worksheets used in Physical Chemistry practicum activities. This study aims to analyze students’ needs for green chemistry-based Student Worksheets to support Physical Chemistry practicum learning. The research employed a descriptive method with a qualitative approach, collecting data through questionnaires and interviews distributed via Google Form. The analysis process included data reduction, data presentation, and conclusion drawing, ensuring that the findings accurately reflected students’ needs for the development of Green Chemistry–based Student WorksheetsThe results indicate that students require worksheets that not only facilitate conceptual understanding but also promote independent learning through safer, more efficient, and environmentally responsible laboratory practices. The findings further show that integrating green chemistry principles into the worksheets has the potential to enhance learning effectiveness and create more sustainable practicum experiences. Therefore, the development of green chemistry-based Student Worksheets is considered crucial for providing valid, practical, and effective learning media that support sustainability-oriented chemistry education in laboratory settings.